EFEKTIVITAS PENGGUNAAN APLIKASI PEMBELAJARAN BERBASIS MOBILE SMARTPHONE SEBAGAI MEDIA PENGENALAN SEJARAH LOKAL MASA REVOLUSI FISIK DI KALIMANTAN SELATAN PADA SISWA SEKOLAH MENENGAH ATAS - Heri Susanto; Helmi Akmal (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This study aims to examine the effectiveness of a learning application that is accessed through mobile smartphones as a medium of introduction of local history during the physical revolution in South Kalimantan. Quantitative method was used with pre-experimental one-group pretest-posttest design in which the researchers tested the effectiveness of the media by comparing the students' understanding before and after being treated. The subjects of the study were students of class XI IPS SMAN 7 Banjarmasin consisting of two classes with a population of 57 people. The sample of this research was 25 students taken from population using sample random sampling technique. The research instrument used in the form of multiple choice test with the number of 25 items. Instrument validity was tested through product moment correlation, while its reliability was tested using alpha cronbach formula. The analysis technique used was paired sample t test with hypothesis H0 = no increase of pretest result to posttest after treatment, and H1 = increase of pretest result to posttest after given treatment. The results showed that after being treated using instructional media application, students' posttest score was greater than pretest with mean posttest (76,80)> pretest (56,32). Through the statistical calculation known that -thitung (-11,058) <-ttabel (-2,064) with a strong and positive correlation of 0.729 which means H1 accepted so that it can be said to occur increased understanding of students after using the application of learning. Based on the results of the study, it was concluded that the application of mobile smartphone-based learning is effectively used as a medium of introduction of local history of physical revolution in South Kalimantan in the students of class XI IPS SMA Negeri 7 Banjarmasin